2021
DOI: 10.1177/01430343211066461
|View full text |Cite
|
Sign up to set email alerts
|

Positive Family Environment, General Distress, Subjective Well-Being, and Academic Engagement among High School Students Before and During the COVID-19 Outbreak

Abstract: The COVID-19 pandemic has altered the family dynamics of most people worldwide as well as the mode in which students take classes. The impact of such changes on students’ well-being, academic engagement, and general distress remains unknown. Therefore, this study aims to test the structural relations among positive family environment (a measure of Positive Home-Based Parent Involvement [HBI]), subjective well-being (SWB), general distress, and academic engagement, focusing on Mexican high school students. A lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…In another study, researchers conducted surveys on the predictors to primary school students' academic engagement. Results indicated that parental involvement, high-quality parentchild relationships, and parental support are all predictors to students' academic engagement, while only clear expectations contributed to perceived competence (Gaxiola Romero et al, 2022).…”
Section: Relationship Between Students' Perceived Parental Expectatio...mentioning
confidence: 96%
“…In another study, researchers conducted surveys on the predictors to primary school students' academic engagement. Results indicated that parental involvement, high-quality parentchild relationships, and parental support are all predictors to students' academic engagement, while only clear expectations contributed to perceived competence (Gaxiola Romero et al, 2022).…”
Section: Relationship Between Students' Perceived Parental Expectatio...mentioning
confidence: 96%
“…The COVID-19 pandemic has seriously affected education as well as other fields (Gaxiola Romero et al, 2022).…”
Section: The Covid-19 Pandemic and Its Reflections On Schoolsmentioning
confidence: 99%
“…The COVID‐19 pandemic has seriously affected education as well as other fields (Gaxiola Romero et al, 2022). Following the first coronavirus case in Turkey on March 12, 2020, distance education was started on March 13, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated the negative impact that school closure had on student performance (Engzell et al, 2021 ; Maldonado & De Witte, 2022 ) as well as on student well-being (Gaxiola Romero et al, 2022 ; Vira & Skoog, 2021 ). During the weeks of school closure, the role of families in supporting student remote schooling increased significantly (Gaxiola Romero et al, 2022 ), although the most prominent role has been played by teachers (Choi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated the negative impact that school closure had on student performance (Engzell et al, 2021 ; Maldonado & De Witte, 2022 ) as well as on student well-being (Gaxiola Romero et al, 2022 ; Vira & Skoog, 2021 ). During the weeks of school closure, the role of families in supporting student remote schooling increased significantly (Gaxiola Romero et al, 2022 ), although the most prominent role has been played by teachers (Choi et al, 2021 ). Given that previous research stressed the link between teachers’ well-being and core measures like teaching effectiveness and student outcomes (Hascher & Waber, 2021 ), it is worth to investigate which factors are related to teachers’ well-being in the context of an Emergency Remote Teaching (ERT) (Portillo et al, 2020 ) like the one created by the Covid-19 crisis.…”
Section: Introductionmentioning
confidence: 99%